Barriers for Local Development Strategic Management Resulting from Personal Qualities of Local Authorities - Sztando, Andrzej (Olsztyn Economic Journal, 2013)
The article discusses the problem of barriers in local development strategic management related to personal qualities of local authorities. In its initial parts the author presents the rationale for their research as well methods he has applied. Then, discusses the key article categories: local development and local development strategic management. Next he lists all identified groups of barriers, referring to such management. In the main part of study, he focuses on these which refer to personal qualities of local authorities. The article results from several years of practice and research conducted by the Author in the domain of local development strategy conceptualization and implementation.